A suite of complementary biocontrol traits allows a native consortium of root‐associated bacteria to protect their host plant from a fungal sudden‐wilt disease. Issue 5 (1st April 2019) - Santhanam, Rakesh; Menezes, Riya C.; Grabe, Veit; Li, Dapeng; Baldwin, Ian T.; Groten, Karin
Abstract: The beneficial effects of plant‐–bacterial interactions in controlling plant pests have been extensively studied with single bacterial isolates. However, in nature, bacteria interact with plants in multitaxa consortia, systems which remain poorly understood. Previously, we demonstrated that a consortium of five native bacterial isolates protected their host plant Nicotiana attenuata from a sudden wilt disease. Here we explore the mechanisms behind the protection effect against the native pathosystem. Three members of the consortium, Pseudomonas azotoformans A70, P. frederiksbergensis A176 and Arthrobacter nitroguajacolicus E46, form biofilms when grown individually in vitro, and the amount of biofilm increased synergistically in the five‐membered consortium, including two Bacillus species, B. megaterium and B. mojavensis . Fluorescence in situ hybridization and scanning electron microscopy in planta imaging techniques confirmed biofilm formation and revealed locally distinct distributions of the five bacterial strains colonizing different areas on the plant‐root surface. One of the five isolates, K1 B. mojavensis produces the antifungal compound surfactin, under in vitro and in vivo conditions, clearly inhibiting fungal growth. Furthermore, isolates A70 and A176 produce siderophores under in vitro conditions. Based on these results we infer that the consortium of five bacterial isolates protects its host against fungal phytopathogens via complementary traits. The study should encourage researchers to create synthetic communities from native strains of different genera to improve bioprotection against wilting diseases.